PENGARUH SEDIAAN DEKOK DAUN ZAITUN (Olea europaea L.) TERHADAP PENURUNAN TEKANAN DARAH PADA TIKUS PUTIH GALUR WISTAR (Rattus norvegicus strain wistar) JANTAN YANG DIINDUKSI NATRIUM KLORIDA 5,5% - Fachri Mubarok; Titik Kusumawinakhyu; Yenni Bahar (Universitas Muhammadiyah Purwokerto, 2020)
According toWHOhypertension about 26.4% of world population who have suffered hypertension. It wouldprobably increase up to 29.2% in 2025. Usually,hypertension medical care uses convensional medicine, however itpossessessome side effects and could causecomplication.For that reason, herbal medicine is needed for safer andmore effective purpose. One of herbal medicines is olive leaf (Olea europea L).It aimed to figure out effect of oliveleaf extract (Olea europaea L.) on declining blood pressurein whitemale rat wistar strain (Rattus novergicus strainwistar) after 5.5% Natrium Chloride (NaCl) induction.24 of rats were divided into 4 groups of treatments and 5.5%NaCl inductions. Group I, as a control withaquadest treatment, Group II was inducted with 540 mgs of olive leafextract, Group III was inducted with 1080mgs of olive leaf extract, and Group IV was inducted with 2160 mgs ofolive leaf extract. Data were Analyzed byOne way ANOVA then followed with Post-hoc test using LeastSignificant Differences (LSD) test. From the group I, the mean of pretest was 117.83/150.83mmHg and the meanof post test was117.83/141.67 mmHg. Group II, the mean of pretest was 123.67/156,00 mmHg and the mean of posttest was87.00/116,00 mmHg. Group III, the mean of pretest was 123.50/156.83 mmHg and the mean of post testwasand the mean of post test was 81.67/112,50 mmHg. Group IV the mean of pretest was 119.00/156.50 mmHgandthe mean of post test was 80.00/105.00 mmHg.There were effects of olive leaf extract (Olea europaea L.) in 540mgs, 1080 mgs and 2160 mgs toblood pressure declining in white male rat wistar strain (Rattus novergicus strainwistar) after 5.5% NatriumChloride (NaCl) induction. The higest blood pressure declining was in Group IV of 2160mg olive leaf extractinduction.